Everest 1922 : The Epic Story of the First Attempt on the World's Highest Mountain - Conefrey, Mick (London : Allen & Unwin, 2022)
The first attempt on Everest in 1922 by George Leigh Mallory and a British team is an extraordinary story full of controversy, drama, and incident, populated by a set of larger-than-life characters straight out of an adventure novel. The expedition ended in tragedy when, on their third bid for the top, Mallory's party was hit by an avalanche that left seven men dead. Using diaries, letters, and unpublished accounts, Mick Conefrey creates a rich, character-driven narrative that explores the motivations and private dramas of the key individuals--detailing their backroom politics and bitter rivalries--who masterminded this epic adventure.
t t Larger Than Life-- t The Gas Offensive-- t 2020 Hindsight.
Includes bibliographical references and index.
Keywords: Mountaineering expeditions -- Everest, Mount (China and Nepal) -- History; Everest, Mount (China and Nepal)